Maize-common bean/lupine intercrop productivity and profitability in maize-based cropping system of Northwestern Ethiopia - Assefa, Alemayehu; Tana, Tamado; Dechassa, Nigusie; Dessalgn, Yigzaw; Tesfaye, Kinde; Wortmann, C.S. (Ethiopian Journal of Science and Technology, 2025)
Cereal-legume intercropping is common in Ethiopia but intercropping of common bean and lupine with maize is a recent practice in maize based cropping system of Northwestern Ethiopia. The objective of this study was to determine the appropriate legume species and planting arrangement for higher productivity and profitability of the cropping system. Field experiments were conducted at two sites in Northwestern Ethiopia during the 2012 and 2013 main cropping seasons. Intercropping of common bean (Phaseolus vulgaris L.), narrow-leaf lupine (Lupinus angustifolius L.), and white lupine (Lupinus albus L.) with maize (Zea mays L.) were conducted under two intercrop planting arrangements (IPA), single row of legume in between maize rows and paired rows of legume in between paired rows of maize and sole cropping of maize as check treatment in randomized complete block design with three replications. Results indicated that maize grain yield was 16% and 13% more on maize-narrow leaf lupine intercropping with paired and single row IPA, respectively, relative to sole crop maize. Maize equivalent yield and land equivalent ratio were on average 18% and 42%, respectively, higher with intercropping compared to sole cropping. Maize-bean with single and paired row IPA, and the maize-narrow leaf lupine with the paired row IPA produced 28%, 23%, and 20% more maize equivalent yield compared to sole crop maize, respectively. The associated increases in net return were 22%, 17%, and 15%. The results indicated enhanced productivity and economic return of maize-common bean intercropping, which could be scaled up for increasing household food security.